David Foster Wallace's Evangelicals: The Other Postsecularism. (June 2018) - Douglas, Christopher
As valuable as postsecularism theory has been for literary studies, it carried the baggage of the secularization thesis. A reading of David Foster Wallace's "Good People" within its political context returns us to the "strong religion" against which postsecularist "weak religion" was initially posed. It is this return of strong religion – as the Christian Right – that has been the most transformational religious development in the postwar United States, even as it continues to be under-remarked in literary studies.